Unveiling the transition: Factors influencing true and fair view reporting in the accrual-based accounting migration of Malaysian federal statutory bodies - Hanafi, Muhammad Aiman Asyraf; Yatim, Norzarina Md; Salim, Abdullah Sallehhuddin Abdullah (Asian Economic and Financial Review, 2024)
This study delves into the factors impacting the adoption of true and fair financial reporting during the transition to accrual accounting in Malaysian Federal Statutory Bodies (FSB). Despite administrative reforms from the 1980s to the most recent reformation, Malaysia’s public sector performance has lagged, prompting this investigation into the adoption of Malaysian Public Sector Accounting Standards (MPSAS) and accrual accounting in response to the delayed performance of Malaysia’s public sector. The research was based on self-administered, Five Likert-scale questionnaires distributed to all heads of public accountants in 132 FSBs. There were 99 questionnaires returned for analysis. The final analysis used 99 usable responses, and the data was analyzed using SPSS. The results indicated significant correlations between Economic Consequences, Political Interventions, and True and Fair View reporting. Economic consequences were found to have the most significant impact on true and fair reporting, supported nuanced relationships, and political interventions. The findings of the regression analysis provided evidence for intricate associations, however, it is important to realize some constraints methods were acknowledged, such as demographic limits and the reliance on quantitative methodologies. The independent Board of Directors (BOD) and the higher-level management ensure those factors, such as the impact of Political Interventions on the reporting process under their scrutiny, as well as take proactive implementation measures to prevent the escalation of the management level from worsening. Top management can ensure that, the economic decisions made have to be thorough, as they dramatically impact reporting. The study provides valuable insights into financial reporting dynamics, suggesting avenues for future research to address identified limitations and incorporate qualitative methodologies.